P4 5 33 Gigawatts to Oblivion: The Explosion That Changed Nuclear History - Fotedar, Ayush; Owusu Boamah, jeremy; McCrea, Alec (Physics Special Topics, 2024)
Reactor 4 at the Chernobyl Nuclear Power Plant experienced a catastrophic power surge on April 26, 1986, caused by a sudden reactivity increase due to the graphite tips of control rods, a positive void coefficient, and steam generation. This paper models the exponential power escalation using point kinetics, finding that the reactor's power surged from 200 MW to over 33 GW in just 4 seconds and would have reached approximately 70 TW within 10 seconds. The analysis highlights the reactor's design flaws and the rapid dynamics of the runaway reaction.